Pacific librarians come together - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
October 1988 a major impetus for cooperation emerged, when CTA, together with USAID, IRETA (the University of the South Pacific's Institute for Research, Extension and Training in Agriculture), and SPC (the Eighth South Pacific Commission) sponsored a sem